Hybrid Methods in Iron-Sulfur Cluster Biogenesis - Prischi, Filippo; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2017)
Hybrid methods, which combine and integrate several biochemical and biophysical techniques, have rapidly caught up in the last twenty years to provide a way to obtain a fuller description of proteins and molecular complexes with sizes and complexity otherwise not easily affordable. Here, we review the use of a robust hybrid methodology based on a mixture of NMR, SAXS, site directed mutagenesis and molecular docking which we have developed to determine the structure of weakly interacting molecular complexes. We applied this technique to gain insights into the structure of complexes formed amongst proteins involved in the molecular machine, which produces the essential iron-sulfur cluster prosthetic groups. Our results were validated both by X-ray structures and by other groups who adopted the same approach. We discuss the advantages and the limitations of our methodology and propose new avenues, which could improve it.